2012
DOI: 10.1371/journal.pone.0033205
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Weight Gain and Body Mass Index in Children: Results from Three German Cohort Studies

Abstract: IntroductionPrevious studies suggested potential priming effects of gestational weight gain (GWG) on offspring’s body composition in later life. However, consistency of these effects in normal weight, overweight and obese mothers is less clear.MethodsWe combined the individual data of three German cohorts and assessed associations of total and excessive GWG (as defined by criteria of the Institute of Medicine) with offspring’s mean body mass index (BMI) standard deviation scores (SDS) and overweight at the age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 33 publications
3
36
2
2
Order By: Relevance
“…Inaccurate or unsafe ideas about ways to contain gestational weight may contribute to the increasing frequency of excess GWG. Avoiding excess GWG is important for women in the long term [20], is associated with better perinatal outcome [4,21-23] and appears to reduce inter-generational transmission of obesity [24] but is not usual. More than half of overweight pregnant women gain in excess of that recommended by the IOM [20,25,26] and this trend is increasing rather than abating [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Inaccurate or unsafe ideas about ways to contain gestational weight may contribute to the increasing frequency of excess GWG. Avoiding excess GWG is important for women in the long term [20], is associated with better perinatal outcome [4,21-23] and appears to reduce inter-generational transmission of obesity [24] but is not usual. More than half of overweight pregnant women gain in excess of that recommended by the IOM [20,25,26] and this trend is increasing rather than abating [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown a positive association between GWG and an increased risk for childhood obesity [23-26], adolescent obesity [27,28], and obesity persisting into adulthood [29-31] propagating a vicious cycle of obesity [9,32,33]. Breaking this cycle at any stage with adequate intervention and prevention strategies is a big challenge.…”
Section: Introductionmentioning
confidence: 99%
“…The details of quantile regression have been described elsewhere[20,21], as has its application to health problems[22,23]. The use of quantile regression with count data is unusual and its application to health forecasting remains novel [24,25].…”
Section: Methodsmentioning
confidence: 99%